2023
DOI: 10.3389/fcell.2023.1070777
|View full text |Cite
|
Sign up to set email alerts
|

A glycolysis-related gene signatures in diffuse large B-Cell lymphoma predicts prognosis and tumor immune microenvironment

Abstract: Background: Diffuse large B-cell lymphoma (DLBCL) is the most common type of lymphoma which that highly aggressive and heterogeneous. Glycolysis has been implicated in the regulation of tumor microenvironment (TME) and development. In this study, we aimed to establish a glycolysis-related prognostic model for the risk stratification, prognosis prediction, and immune landscape evaluation in patients with DLBCL.Methods: Three independent datasets GSE181063, GSE10846, and GSE53786 containing gene expression profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…B cells as immunomodulatory cells, positive mediators, and antigen-presenting cells play a role in modulating the immune response to cancer ( 83 ). We found that DLBCL with high CISD2Risk value exhibited increased B cell infiltrations in accord with several studies ( 47 , 77 , 84 , 85 ). B cells are part of the adaptive immune system and can produce antibodies against cancer cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…B cells as immunomodulatory cells, positive mediators, and antigen-presenting cells play a role in modulating the immune response to cancer ( 83 ). We found that DLBCL with high CISD2Risk value exhibited increased B cell infiltrations in accord with several studies ( 47 , 77 , 84 , 85 ). B cells are part of the adaptive immune system and can produce antibodies against cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…We introduced the ESTIMATE algorithm to infer the fraction of stromal and immune cells in tumour samples based on single sample gene set enrichment analysis (ssGSEA). A higher stromal ( P < 0.05, Figures 6A, D ) or immune scores ( P < 0.05, Figures 6B, E ) suggested greater density of stromal or immune cells in the tumour immune microenvironment of DLBCL patients with low CISD2Risk value the ESTIMATE scores that represent the sum of the stromal or immune scores, which can infer tumour purity associated with poor prognosis ( 29 , 45 ), were negatively correlated with CISD2Risk value ( 46 , 47 ) ( P < 0.05, Figures 6C, F ). The CIBERSORT algorithm ( 30 ) was used to estimate the distribution and proportion of 22 immune cell types in DLBCL.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, the metabolic status, such as glycolysis, of exhausted CD8 + TILs is reported to be abnormally active and is related to the resistance to ICB therapy [ 45 ]. A recent study has shown that the abnormal expression of glycolysis-related signature genes in DLBCL is related to the infiltration of CD8 + TILs and TIM3 expression [ 46 ], suggesting the possible role of glycolysis in TIM3/Galectin-9 pathway mediated CD8 + TILs exhaustion in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…A workable strategy for risk classi cation and focused gene identi cation is bioinformatics analysis based on sequenced RNA data. Although risk analyzed rely on immune cell in ltration and energy metabolism have been developed by researchers [23,33,34] , our work has particular advantages over earlier research. First, by consensus clustering, two molecular clusters with noticeably contrasting outlooks and immunological states were found in our studies on glycolysis in patients with DLBCL.…”
Section: Discussionmentioning
confidence: 99%